Low‐Dimensional Organic Tin Bromide Perovskites and Their Photoinduced Structural Transformation. (3rd July 2017) - Zhou, Chenkun; Tian, Yu; Wang, Mingchao; Rose, Alyssa; Besara, Tiglet; Doyle, Nicholas K.; Yuan, Zhao; Wang, Jamie C.; Clark, Ronald; Hu, Yanyan; Siegrist, Theo; Lin, Shangchao; et al.
Abstract: Hybrid organic–inorganic metal halide perovskites possess exceptional structural tunability, with three‐ (3D), two‐ (2D), one‐ (1D), and zero‐dimensional (0D) structures on the molecular level all possible. While remarkable progress has been realized in perovskite research in recent years, the focus has been mainly on 3D and 2D structures, with 1D and 0D structures significantly underexplored. The synthesis and characterization of a series of low‐dimensional organic tin bromide perovskites with 1D and 0D structures is reported. Using the same organic and inorganic components, but at different ratios and reaction conditions, both 1D (C4 N2 H14 )SnBr4 and 0D (C4 N2 H14 Br)4 SnBr6 can be prepared in high yields. Moreover, photoinduced structural transformation from 1D to 0D was investigated experimentally and theoretically in which photodissociation of 1D metal halide chains followed by structural reorganization leads to the formation of a more thermodynamically stable 0D structure.